Determination of vertebral range of motion using inertial measurement units in 27 Franches‐Montagnes stallions and comparison between conditions and with a mixed population. (14th July 2015) - Heim, C.; Pfau, T.; Gerber, V.; Schweizer, C.; Doherr, M.; Schüpbach‐Regula, G.; Witte, S.
Summary: Reasons for performing study: The diagnosis of equine back disorders is challenging. Objectively determining movement of the vertebral column may therefore be of value in a clinical setting. Objectives: To establish whether surface‐mounted inertial measurement units (IMUs) can be used to establish normal values for range of motion (ROM) of the vertebral column in a uniform population of horses trotting under different conditions. Study design: Vertebral ROM was established in Franches‐Montagnes stallions and a general population of horses and the variability in measurements compared between the two groups. Repeatability and the influence of specific exercise condition (on ROM) were assessed. Finally, attempts were made to explain the findings of the study through the evaluation of factors that might influence ROM. Methods: Dorsoventral (DV) and mediolateral (ML) vertebral ROM was measured at a trot under different exercise conditions in 27 Franches‐Montagnes stallions and six general population horses using IMUs distributed over the vertebral column. Results: Variability in the ROM measurements was significantly higher for general population horses than for Franches‐Montagnes stallions (both DV and ML ROM). Repeatability was strong to very strong for DV measurements and moderate for ML measurements. Trotting under saddle significantly reduced the ROM, with sitting trot resulting in a significantly lower ROM than rising trot. Age is unlikely to explain the low variability in vertebral ROM recorded in the Franches‐Montagnes horses, while this may be associated with conformational factors. Conclusions: It was possible to establish a normal vertebral ROM for a group of Franches‐Montagnes stallions. While within‐breed variation was low in this population, further studies are necessary to determine variation in vertebral ROM for other breeds and to assess their utility for diagnosis of equine back disorders.